2005
DOI: 10.1177/102490790501200109
|View full text |Cite
|
Sign up to set email alerts
|

Going to the Multidisciplinary Case Conference for Child Abuse: A Review and Guide to the Medical Practitioner

Abstract: Multidisciplinary case conference is an important component in the management of suspected cases of child abuse and neglect in Hong Kong. The medical practitioner is one of the key professionals in the case conference to discuss the nature of the case, issues concerning child protection, and interventions to safeguard the child's subsequent welfare interests. Yet, specific guidance for the medical profession is lacking. In this article, the authors present an overview of the child protection case conference an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For example, community nurses in Northern Ireland were found more inclined to alert and report suspicions of child physical abuse than doctors (Lazenbatt & Freeman, 2006). Lee et al (2005) also found that inconsistencies in the understanding of child abuse were common among social workers, nurses and medical practitioners as the acceptable standard on the use of physical punishment in Hong Kong was absent.…”
Section: Introductionmentioning
confidence: 99%
“…For example, community nurses in Northern Ireland were found more inclined to alert and report suspicions of child physical abuse than doctors (Lazenbatt & Freeman, 2006). Lee et al (2005) also found that inconsistencies in the understanding of child abuse were common among social workers, nurses and medical practitioners as the acceptable standard on the use of physical punishment in Hong Kong was absent.…”
Section: Introductionmentioning
confidence: 99%